Understanding the association between exposure to family planning messages and consistent condom use among never married men in Ghana. - Bright Opoku Ahinkorah (Public Library of Science (PLoS), 2021)
Background Despite considerable efforts to promote condom use, sexually active people in sub-Sahara Africa still engage in risky sexual behaviours, with condom use relatively low. With this high vulnerability of these persons to HIV and sexually transmitted infections, research related to exposure to family planning messages to help curb this trend remains sparse. This study examined how exposure to family planning messages in the midst of some socio-demographic factors is associated with consistent condom use among sexually active never married men in Ghana. Methods Data were obtained from the 2014 Demographic and Health Survey (DHS) of Ghana. Only never married men (15-64 years) who have had sexual experience in the last 12 months were included in the analysis (N = 971). Frequencies, percentages, chi-square tests and binary logistic regression analyses were carried out. Results of the binary logistic regression analysis were presented using crude odds ratios (cOR) and adjusted odds ratios (aOR). Results The results showed that only 26.15% of sexually active never married men in Ghana consistently used condom during sex. Men who were exposed to family planning messages were 51% more likely use condom consistently compared to those who are not exposed [aOR = 1.51, CI = 1.04-2.18]. In terms of the covariates, the likelihood of consistent condom use among men in Ghana was lower among those aged 35 years and above compared to those aged 15-24 [aOR = 0.46 CI = 0.21-0.99]. The odds of consistent condom use among men increased with level of education, with men with higher level of education having the highest odds of consistent condom use compared to those with no formal education [aOR = 9.98, CI = 2.05-48.46]. Men of the richest wealth quintile were more likely to use condom consistently compared to those of the poorest wealth quintile [aOR = 2.62, CI = 1.30-5.27]. Higher odds of consistent condom use was found among men who dwelled in the Central, Northern, and Upper East regions compared to those of the Western region. Conclusion Our findings have established a strong association between exposure to family planning messages alongside age, educational level, wealth, and region of residence and consistent condom use. Men exposed to family planning messages were more likely to use condoms consistently. Designed programs should use intervention strategies that focus on interactive and participatory educational activities to improve sexually active men's interpersonal communication on family planning messages, especially on consistent condom use with their sexual partners.